2010
DOI: 10.1161/circulationaha.109.904672
|View full text |Cite
|
Sign up to set email alerts
|

B Vitamins and the Risk of Total Mortality and Cardiovascular Disease in End-Stage Renal Disease

Abstract: Background-In observational studies, hyperhomocysteinemia has been found to be a risk factor for total mortality and cardiovascular events in patients with end-stage renal disease. These patients have grossly elevated homocysteine levels that can be lowered by supplementation with folic acid and vitamin B 12 . We conducted a randomized clinical trial with B vitamins to reduce homocysteine levels and therefore cardiovascular events and total mortality. Methods and Results-This randomized, double-blind multicent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
90
0
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 121 publications
(95 citation statements)
references
References 26 publications
3
90
0
2
Order By: Relevance
“…Wrone et al (13) Righetti et al (14) Zoungas et al (12) House et al (21) Heinz et al (22) Overall 0·159537 One report demonstrated that endothelial cells can develop abnormal vasoreactivity and may adopt a prothrombotic phenotype and secrete leucocyte chemotactic factors, adhesion molecules and inflammatory cytokines when exposed to elevated Hcy (23) . Endothelial dysfunction is a key process in atherosclerosis, which independently predicts CVD events (24) ; and it becomes progressively more common as renal function declines (25) .…”
Section: Studymentioning
confidence: 99%
See 3 more Smart Citations
“…Wrone et al (13) Righetti et al (14) Zoungas et al (12) House et al (21) Heinz et al (22) Overall 0·159537 One report demonstrated that endothelial cells can develop abnormal vasoreactivity and may adopt a prothrombotic phenotype and secrete leucocyte chemotactic factors, adhesion molecules and inflammatory cytokines when exposed to elevated Hcy (23) . Endothelial dysfunction is a key process in atherosclerosis, which independently predicts CVD events (24) ; and it becomes progressively more common as renal function declines (25) .…”
Section: Studymentioning
confidence: 99%
“…Also, to the best of our knowledge, there are no studies that have determined a threshold value for Hcy level for effective prevention of cardiovascular events in the general population or in patients with CKD. Observational data in a meta-analysis show that a 25 % reduction in Hcy was associated with a 32 % lower risk of CVD among Study Righetti et al (16) Wrone et al (13) Righetti et al (14) Zoungas et al (12) Jamison et al (20) Nanayakkara et al (18) Vianna et al (17) Mann et al (19) House et al (21) Heinz et al (22) Overall 0·074931 …”
Section: Studymentioning
confidence: 99%
See 2 more Smart Citations
“…[28] However, findings from trials on Hcy-lowering therapy with folic acid or B-vitamins (containing folic acid) in stroke prevention have been mostly negative. [29][30][31] A meta-analysis of relevant trials revealed that most previous trials were conducted in countries with high folic acid consumption [32,33] and that mandatory folate fortification of the grain supply in those countries may have reduced the Hcy levels in the total population and affected the power of the trials to detect a positive effect. Consistently, our recent meta-analysis found that lowering Hcy concentration by folic acid supplementation significantly reduced the progression of carotid intima-media thickness, [34] the risk of cardiovascular diseases in patients with chronic kidney disease, [35] and the risk of stroke, [36] particularly in those without dietary folic acid fortification.…”
Section: Discussionmentioning
confidence: 99%